MENINGKATKAN KEMANDIRIAN SISWA MENGGUNAKAN MODEL BAIRIK MEDIA WORDWALL DI SDN SUNGAI JINGAH 4 - Yunita; Diani Ayu Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this research is the low level of student independence caused by students' lack of awareness of independent learning. In learning, it can be seen that students tend to depend on friends, do not have confidence in themselves so they are embarrassed to express opinions, miss bringing books, do not have their own initiative in studying, and often disturb friends when learning. To overcome the problems, the BAIRIK (Problem Based Learning, Numbered Head Together, and Talking Stick) learning model was applied. The aim of this research is to increase student independence. This research used a type of Classroom Action Research (PTK). The results of this research show that student independence at meeting 1 reached 35% with the criteria for being less independent, increasing at meeting 4 to 95% with the criteria for being very independent. Based on these findings, it can be concluded that the BAIRIK learning model can increase student independence.